2019
DOI: 10.1007/s00198-019-04857-3
|View full text |Cite
|
Sign up to set email alerts
|

The muscle-bone unit in adolescent swimmers

Abstract: 3 EXERNET red de investigación en ejercicio físico y salud para poblaciones especiales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The importance of muscular fitness lies in its inverse association with total and central adiposity and therefore with cardiovascular diseases and metabolic risk factors, and its positive association with bone health [ 15 ] and self-esteem [ 16 ]. Children and adolescents with overweight and obesity show higher maximal muscular strength than children and adolescents with normal weight because the excess of weight involves a chronic training stimulus during the activities of daily living [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of muscular fitness lies in its inverse association with total and central adiposity and therefore with cardiovascular diseases and metabolic risk factors, and its positive association with bone health [ 15 ] and self-esteem [ 16 ]. Children and adolescents with overweight and obesity show higher maximal muscular strength than children and adolescents with normal weight because the excess of weight involves a chronic training stimulus during the activities of daily living [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there is a standardized database reference for the BMD T value of the lumbar vertebrae and hip joint, there is no database comparison for the local BMD of the knee joint. Previous studies have shown no difference in the bone mass between the dominant and non-dominant sides in the lower extremities (23)(24)(25). Analysis of the local bone density of the knee joint for 20 healthy subjects showed similar results in the bilateral legs.…”
Section: Measure Methods Of Bmdmentioning
confidence: 50%
“…Previous research has shown positive relationships between MBR and performance measures 33 34 . Gomez-Bruton et al 35 , demonstrated differing structural muscle-bone unit ratios (ratio of BMC and LM) between adolescent swimmers and controls, with swimmers demonstrating lower ratios compared to controls. This indicates adolescent swimmers having a lower amount of BMC for similar amount of LM, or similar BMC and higher LM.…”
Section: Discussionmentioning
confidence: 97%